(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
The article deals with the problem of using modern information technologies in the educational process in the form of interactive training programs and computer tests.Their advantages, restrictions and place in the educational process as well as their influence on quality of education are considered.